Tourists' willingness to pay for Blue Flag's new ecolabel for sustainable boating: the case of whale-watching in Iceland. Issue 4 (7th August 2020) - Lissner, Isabel; Mayer, Marius
ABSTRACT: Despite its positive image boat-based marine wildlife tourism, including whale-watching, endangers animals' habitats and populations. This highlights the importance of transitioning towards more sustainable forms of boating. This could be achieved through certification with ecolabels that establish clear guidelines for operators, and ensure compliance, while informing tourists of these higher standards. Ecolabelled operators should be able to gain a competitive edge by offering a more sustainable product. The aim of this paper is to analyse tourists' willingness to pay for a new ecolabel for sustainable boating in the case of whale-watching in Iceland using the Contingent Valuation Method. Results of a survey of 337 whale-watchers show that 60% were very likely to choose an ecolabelled tour, and that 65.9% were likely or very likely to be willing to pay ∼20% more for an ecolabelled tour. Considering the intention-behaviour gap, the low importance of environmental issues for choosing the operator, and other biases, it is probable that the ecolabel would only influence preferences in a limited market niche. We suggest that the new ecolabel has a high potential for promoting sustainability in boating tourism if it develops into a full-blown CSR approach that covers a content broader than just environmental issues.